STUDENT PERFORMANCE IN EMERGENCY REMOTE LEARNING AND ASSESSMENT IN SIMULTANEOUS INTERPRETING TRAINING - Krouglov, Alex (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The paper covers some issues of student performance in Simultaneous Interpreting modules during the emergency remote training in March – June 2020 when many universities around the world had to switch quickly to online synchronous training. Simultaneous Interpreting was chosen for this research since the existing IT platforms for online training are not sufficient in view of the complexity of simultaneous interpreting training which requires special equipment and the availability of two channels of communication. The research explores the main challenges facing trainers and students when they had to move to emergency online teaching and learning and assesses the performance of students in synchronous online simultaneous classes and final examinations or assessments. The study is based on qualitative methods guided by grounded theory and engaged 17 teachers and 24 students at seven universities teaching Simultaneous Interpreting modules. The results of the research showed that the move to emergency remote teaching and learning did not have any significant impact on the performance of students and their assessment in the remaining part of the module. Academic teams came up with a number of innovative solutions for remote teaching, learning and assessment which should be studied further in order to develop effective tools which could be used in synchronous online simultaneous interpreting teaching and learning in the future.